CHARACTERIZATION OF FRUIT ON SEVERAL SALAK VARIETIES AND THEIR HYBRIDS - Sri Hadiati; T. Budiyanti; A. Soemargono; A. Susiloadi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
The objective of this study was to characterize salak of local varieties and their hybrids. The fruits characterized were taken from plants that were grown in October 2004. The results revealed that fruits ³ 61 g were mostly produced by hybrids, in which one of their parents was Mwr or Ph. Fruits with flesh thickness ³ 0.85 cm were mostly yielded from Sdp, Sdm, and hybrids where one of their parents was Sdp or Mwr. While fruits with edible portion ³ 65.0% were mostly yielded from Sdp, Gp, and hybrids where their female parents were Mwr, Ph, and Sdp. Fruits with small seeds (≤ 3.0 g) were observed on Gp, whilst those with big seeds (≥ 7.0 g) were on Sdm, Sdm-Sj and Sdp-Sj. Hybrids from the female of Ph and Sdp mostly gave sweet taste (TSS ≥ 20º Brix). Mwr x Sdp crossing produced non-astringent fruits, while Ph x Java (K, M, Mj), Sdp x Sjg and some Sdp x Mwr crossing as well as Mwr produced astringent fruits. The four superior characters, namely fruit ≥ 61 g, flesh thickness ³ 0.85 cm, edible portion ≥ 65%, and TSS ≥ 20º Brix were found in Mwr-Sp-8, Sdp-Sj-8, and Ph-M-7. Fruits produced by Mwr-Sp-8 were not astringent, while those produced by Sdp-Sj-8 and Ph-M-7 were astringent. These findings suggest that the selection of parent can play an important role in improving the varieties of salak. Keywords: salak, characterization, variety, hybrid, fruit